The Rise of Digital Platforms – Effects on Competition - Pirimova, Vera; Mancheva, Ivanina (Research Papers, 2021)
The study focuses on multi-sided markets (platforms) as a specific materialization of competition in a digital context. We describe the determinants of the rise of platforms and their effects on competition. Stemming from digitalization, network effects, economies of scale, high sunk costs and high switching costs lead to lock-ins. This changes the nature of competition as well as some key features of value creation in traditional markets of goods and services. These challenges are considered in terms of possible regulatory solutions.